Al-Qaeda in East Africa and the Horn - Shinn, David (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2007)
Al-Qaeda has had greater success in East Africa and the Horn than any other part of sub-Sahara Africa. Relative proximity to the Middle East and a series of local factors account for this situation. Al-Qaeda carried out the bombings of the US embassies in Kenya and Tanzania in 1998 and bombed an Israeli-owned hotel in Kenya north of Mombasa in 2002. Local and international authorities foiled a number of other al-Qaeda plots in the region. Osama bin Laden had his headquarters in Sudan from late 1991 until Sudan forced him to leave in mid-1996. Subsequent al-Qaeda efforts, which were already well advanced in Kenya and Somalia, tended to emanate from those two countries. But while acknowledging there is a real al-Qaeda problem in the region, there is a tendency by the US, a few countries in the region, and al-Qaeda itself to exaggerate its impact and influence. This only plays into the hands of al-Qaeda and focuses scarce US resources primarily on the short-term goal of tracking down al-Qaeda while reducing attention and resources for dealing with the long-term reasons why al-Qaeda has been able to function in the region. Eliminating al-Qaeda is important but it will not be accomplished solely by military action against suspected al-Qaeda operatives. It is time to confront this as a long-term challenge that addresses more effectively its root causes.